Tribomechanical Properties of the Modified Surface of Alloys of the WC-Co System - Oskolkova Tatyana (EDP Sciences, 2021)
The research results of tribological characteristics of the surface hardened by electric explosion alloying of tungsten-cobalt hard alloys with carbon, titanium and aluminum are presented. The correlation of tribomechanical properties of the modified surface of alloys with changes in the structure and phase composition of the surface layer of the material is established. It is shown that the best wear characteristics are achieved during hardening of alloys by electric explosion of titanium. In this case, the coefficient of friction decreases by almost 3 times, the wear resistance estimated by the depth of the wear track increases by more than 10.0 times, and by the area of the wear track – by 53.2 times.